MUTU FISIK, KIMIA DAN ORGANOLEPTIK BUAH TOMAT (Lycopersicum esculentum Mill.) HASIL PELAPISAN BERBAGAI JENIS PATI SELAMA PENYIMPANAN - Abdi, Yudha Alimba; Rostiati, Rostiati; Kadir, Syahraeni (AGROTEKBIS, 2017)
This study aims to determine the quality of the physical, chemical and organoleptic tomatoes coating results of various types of starch during storage. The research location is in Laboratories of Agroindustry, Faculty of Agriculture, University Tadulako, Palu, and it conducted from March to April 2016. The research method used was a completely randomized design (CRD), which consists of 6 treatment types of starch ie starch taro, sugar palm starch, sago starch, tapioca starch, rice starch and without starch coating (control), the whole treatment was repeated three times, thus btained 18 experimental units. The results of the research showed that consumers in particular organoleptic (panelists) are relatively more like tomatoes without coating various types of starch. As for the physical and chemical quality of tomatoes is comparatively better until the third week of storage, except on sugar and vitamin C when compared with tomato fruit coating results of various types of starch. Therefore naturally tomatoes coated layer of wax on the surface of the fruit causes the starch solution to "edible coating" is difficult to stick to the surface of the fruit. Emulsifer which required the administration is able to bridge the two compounds wax on the surface of the tomato fruit and starch as a coating compound.Â Key words: Organoleptic, physical, chemical, Tomatoes.